Therapeutic strategies to avoid long term adverse outcomes of neonatal antiepileptic drug exposure - Forcelli, Patrick A. (2010)
Antiepileptic drugs (AEDs) such as phenobarbital, phenytoin and valproic acid, when given in therapeutic doses to neonatal rats, cause pronounced neuronal apoptotic cell death. This effect is especially pronounced in the striatum and cortex during the second postnatal week; a period corresponding to the “brain growth spurt” (third trimester of gestation and early infancy) in humans. Of particular concern is the fact that phenobarbital is the most frequently used therapy for neonatal epilepsy. If AED-induced neuronal cell death leads to long-term functional impairment, then it becomes crucial to find therapies that avoid this neurotoxicity in the sensitive period. Here we examine short and long-term functional effects following exposure of neonatal rat pups to phenobarbital; the functions tested include striatal GABAergic synaptic responses and reflex development in pups, and fear conditioning, emotionality, and sensory-motor gating in adults. In all cases, phenobarbital exposure during the second postnatal week was sufficient to cause significant impairment. In contrast, adult animals exposed as pups to lamotrigine (given in a dose that does not cause apoptotic neuronal death) were not impaired on the tasks we examined. Our data suggest that treatments devoid of proapoptotic actions may be promising therapies for avoiding adverse outcomes after neonatal exposure. In addition, our findings identify early exposure to certain AEDs as an important potential risk factor contributing to psychiatric and neurological abnormalities later in life.